The civil liability of the notary public for his own actions and for the actions of others A study in light of the UAE legislation - Aldhoori, Jasim Mousa; Sadat, Mohamed Mohamed (Journal of Economic, Administrative and Legal Sciences, 2022)
The judicial function has an influential role in stabilizing relations between members of society, and there must be a clerk who assists the judge in his work, to carry one of the burdens of the judicial function on behalf of him. The notary public is one of the basic facilities in the judiciary, as he performs the tasks and competencies specified by law, and the UAE legislator explained in the Federal Law No. 4 of 2013 in Article (1) related to definitions of the law regulating the profession of notary public, as a legally competent person who performs the functions mentioned in the law, and it includes two types; They are: the public notary and the private notary. The UAE legislator defined the notary as anyone who is approved by the department or assigned to perform specific legal tasks, including ratification of documents and papers. The notary public works through the court’s headquarters and from outside, as the state has taken great strides towards developing and facilitating the mechanism for providing the services of the notary, as he provides his services from places outside the court, and his working hours extend for more than 8 hours, moreover that he provides documentation and certification services. Recently, the courts in the United Arab Emirates have licensed many lawyers to practice the profession of private notary from within their offices, which made it easier for the public to receive the service according to mechanisms and timings that meet the aspirations and needs of many businessmen and the public. The UAE legal system - in general - and Federal Law No. (4) for the year 2013 on the organization of the profession of notary public- in particular –put on the responsibility of the notary public a set of professional duties, and refers to those duties of those obligations that are directly related to his profession, i.e. the obligations of which breach constitute crimes that require criminal or civil liability or both, in addition to disciplinary liability if they are committed during the exercise of the job or on the occasion of it. Since the notary public is a public employee, and his profession is not an authority or a privilege that makes its exercise beyond accountability, but rather it is a public service, and assigning those responsible for it to be the purpose of the assignment is to be the service of the individuals and the public. And if the notary public fails to perform that service or deviate the way of right, he must be held accountable and just punishment on him become a must, as a penalty for this failure, or deviation from the right. Since the civil responsibility is the focus of our research, which derives its strength and value from the documentation profession, as it is related to the conclusion of contracts between the contracting parties, the keeping of the professional secrets during writing and the non- disclosure of secrets, this responsibility takes several forms as a responsibility and emanating from personal action or by the act of others, nor it is hidden from the legal researcher what the differences exist between the contractual responsibility system and the responsibility for the harmful act, whether in terms of the basis, nature or function, which justifies the existence of the two existing systems within the framework of that civil responsibility, whether it is related to one of the two.